International multicenter expert survey on endoscopic treatment of upper gastrointestinal anastomotic leaks - Rodrigues-Pinto, Eduardo; Repici, Alessandro; Donatelli, Gianfranco; Macedo, Guilherme; Devière, Jacques; van Hooft, Jeanin E.; Campos, Josemberg M.; Galvao Neto, Manoel; Silva, Marco; Eisendrath, Pierre; Kumbhari, Vivek; Khashab, Mouen A. (Endoscopy International Open, 2019)
Background and study aims A variety of endoscopic techniques are currently available for treatment of upper gastrointestinal (UGI) anastomotic leaks; however, no definite consensus exists on the most appropriate therapeutic approach. Our aim was to explore current management of UGI anastomotic leaks. Methods A survey questionnaire was distributed among international expert therapeutic endoscopists regarding management of UGI anastomotic leaks. Results A total of 44 % of 163 surveys were returned; 69 % were from gastroenterologists and 56 % had > 10 years of experience. A third of respondents treat between 10 and 19 patients annually. Fifty-six percent use fully-covered self-expandable metal stents as their usual first option; 80% use techniques to minimize migration; 4 weeks was the most common reported stent dwell time. Sixty percent perform epithelial ablation prior to over-the-scope-clip placement or suturing. Regarding endoscopic vacuum therapy (EVT), 56 % perform balloon dilation and intracavitary EVT in patients with large cavities but small leak defects. Regarding endoscopic septotomy, 56 % consider a minimal interval of 4 weeks from surgery and 90 % consider the need to perform further sessions. Regarding endoscopic internal drainage (EID), placement of two stents and shorter stents is preferred. Persistent inflammation with clinical sepsis was the definition most commonly reported for endoscopic failure. EVT/stent placement and EVT/EID were the therapeutic options most often chosen in patients with previous oncologic surgery and previous bariatric surgery, respectively. Conclusions There is a wide variation in the management of patients with UGI anastomotic leaks. Future prospective studies are needed to move from an expert- to evidence- and personalization-based care.